(untitled) - Long-Term outlook committee, economic council, economic planning agency (Tokyo, 1983)
Population Aging in Japan: Problems and Policy Issues in 21st Century. International Case of Japan." Prepared for the International Conference on Population and Family Planning, Japan in the Year 2000. Preparing Japan for an Age of Internationalization, the Aging Society and Maturity.
Keywords: Lão hóa dân số,Population aging; Khía cạnh dân số,Economic aspects; Nhật Bản,Japan